An improved characteristic length method for predicting the single bolt joint bearing strength considering secondary bending effect. Issue 10 (15th April 2022) - Qiu, Cheng; Guan, Zhidong; Du, Shanyi
Abstract: This paper puts forward a new method to predict the bearing strength of single bolt joint based on characteristic length method (CLM) and progressive damage model (PDM). Instead of performing the whole campaign of PDM-based CLM on whole structure of joint, the characteristic length and stress distribution of the sub-laminates obtained by dividing the original laminate are used. Stress gradient along the thickness, which is caused by the secondary bending effect of single-lap joint, can be taken into consideration. 3D progressive damage models are established for obtaining the bearing response of sub-laminate with emphasis on fiber kinking theory, where an interpolation algorithm is adopted to find the kinking plane and corresponding kinking angle. Both numerical models and experiments are utilized to verify our scripts of new method. It is concluded that the bending effect can be successfully considered and the proposed method shows advantages for the structural design of mechanically joints. Highlights: A new method is put forward by dividing the original laminate into sub-laminates to account for secondary bending effect. A progressive damage model based characteristic length method is employed to predict failure of each sub-laminate. The kink band theory is used for the interpretation of the mechanism of fiber compressive damage and a zero-thickness cohesive method is used for interlaminar damage. An interpolation algorithm is adopted to find the kinking plane while a graphic method is used to obtain the kinking angle.